1999
DOI: 10.1046/j.1365-2842.1999.00416.x
|View full text |Cite
|
Sign up to set email alerts
|

Wear of composite resin veneering materials in a dual‐axis chewing simulator

Abstract: The attritional wear of human enamel and four different composite resins for the veneering of crowns was evaluated in a dual-axis chewing simulator over up to 1200000 loading cycles. Enamel showed less wear than the composite resins. However, an ultrafine compact-filled composite resin (Targis) showed a wear not statistically significantly different from that of enamel. The other composite resins showed a statistically significantly higher wear than enamel regardless whether microfine, ultrafine midway-filled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
140
1
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(154 citation statements)
references
References 25 publications
4
140
1
4
Order By: Relevance
“…1,6,8,9,22 Clinical studies are time consuming and in addition, it is often difficult to standardise the test parameters. 20 Therefore, long-term results regarding the marginal fit can be obtained by in vitro tests. The results obtained after 240,000 to 250,000 'masticatory' cycles in a chewing simulator corresponded to the results obtained after one year of clinical service.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,6,8,9,22 Clinical studies are time consuming and in addition, it is often difficult to standardise the test parameters. 20 Therefore, long-term results regarding the marginal fit can be obtained by in vitro tests. The results obtained after 240,000 to 250,000 'masticatory' cycles in a chewing simulator corresponded to the results obtained after one year of clinical service.…”
Section: Discussionmentioning
confidence: 99%
“…Excess polymerised composite was removed with a scalpel and a fine finishing diamond. Then, half of the specimens of the three groups were artificially aged in a computer controlled dual axis chewing simulator (Willytec, Munich, D) 20 (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, there have been several in vitro [4][5][6] and in vivo studies 7,8 of the properties of these composites and promising results have been reported for crowns, 9 and for fixed partial dentures. 10 However, although these materials seem to provide excellent aesthetics, 11 some authors do not recommend composite materials for permanent restorations, 12,13 because of their unstable aesthetics, their increased wear 14 and their liability to plaque accumulation. 15 With the introduction of fiber reinforced composites, it seemed to be possible to eliminate these disadvantages of composites and to exploit their advantages, including the simple laboratory procedure, the lower costs and the possibility of repair.…”
Section: Introductionmentioning
confidence: 99%
“…Diante do seu rápido aperfeiçoamento, combinado com o uso dos sistemas adesivos, a resina composta hoje em dia é utilizada na maioria das restaurações estéticas diretas em dentes anteriores 3,8 , solucionando um número cada vez maior de situações clínicas de alterações de função, forma e estética [8][9][10] , sob um conceito de intervenção operatória minimamente invasiva 11 . Contudo, o profissional deve conhecer os limites do material para oferecer e optar pelo melhor tratamento diante desses casos de reabilitação.…”
Section: Introductionunclassified